1999
DOI: 10.1016/s0375-9474(98)00649-6
|View full text |Cite
|
Sign up to set email alerts
|

Antikaon production and medium effects in heavy-ion collisions at AGS

Abstract: Antikaon production from heavy ion collisions at energies available from the Alternating Gradient Synchrotron (AGS) at the Brookhaven National Laboratory is studied in a relativistic transport (ART) model. We include contributions from the baryon-baryon, meson-baryon, and meson-meson interactions. The final-state interaction of antikaons via both absorption and elastic scattering by nucleons and pions are also considered. To compare with presently available or future experimental data, we have calculated the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…v 1 for K + is similar to proton flow (normal flow) and K − flow is anticorrelated (anti-flow) in hybrid mode. Our results are in disagreement with observations reported in [58,59]. Experimentally, it is found that K + shows anti-flow and K − shows normal flow as nucleons due to different potentials they experience while propagating through medium derived from the effective chiral models [60].…”
Section: Rapidity Dependencecontrasting
confidence: 99%
“…v 1 for K + is similar to proton flow (normal flow) and K − flow is anticorrelated (anti-flow) in hybrid mode. Our results are in disagreement with observations reported in [58,59]. Experimentally, it is found that K + shows anti-flow and K − shows normal flow as nucleons due to different potentials they experience while propagating through medium derived from the effective chiral models [60].…”
Section: Rapidity Dependencecontrasting
confidence: 99%
“…Kaon elastic scatterings with nucleons and baryon resonances are included with a constant cross section of 10 mb [14]. Antikaon elastic scatterings with nucleons and inelastic channels, such as K(N ∆N * ) ↔ π(ΛΣ), are included [81] using parameterized experimental data [82]. Also included are kaon production channels involving three-body final states, (πρω)(N ∆N * ) → K KN [81].…”
Section: The Art Modelmentioning
confidence: 99%
“…Antikaon elastic scatterings with nucleons and inelastic channels, such as K(N ∆N * ) ↔ π(ΛΣ), are included [81] using parameterized experimental data [82]. Also included are kaon production channels involving three-body final states, (πρω)(N ∆N * ) → K KN [81]. Because of the difficulty associated with the three-body kinematics, the inverse kaon annihilation reactions of the above channels are neglected.…”
Section: The Art Modelmentioning
confidence: 99%
“…The predictions of the theoretical approaches, outlined above, on kaon properties in dense matter can be tested by analyzing proton-nucleus and heavy-ion collision data on kaon spectra, excitation functions (see Section 3.4) and collective flow [34,[99][100][101][112][113][114][115]. The latter observable was also recognised as Figure 16: The K + spectra from CBUU calculations (solid lines) in comparison to the data from the ANKE Collaboration [123,127] for p+C reactions at 1.0, 1.2, 1.5, 2.0 and 2.3 GeV .…”
Section: Determination Of the K + -Nucleus Real Potentialmentioning
confidence: 99%